Decadal variations in near-surface wind speed across the Northern Hemisphere on a centennial timescale and their possible causes - Lin-Wei Li; Jin-Lin Zha; Ting Chuan; Jian Wu; De-Ming Zhao; Wen-Xuan Fan; Yan-Jun Lyu; Hui-Ping Jiang (Advances in Climate Change Research)
The reduction in near-surface wind speed (NSWS), followed by its recent recovery, could be a feature of decadal variations. However, existing studies mainly analyse the characteristics and causes of NSWS changes on regional scales and over short periods. The decadal variations and underlying causes of global NSWS changes over long timescales remain underexplored. In this study, we investigated the characteristics of NSWS changes in the Northern Hemisphere (NH) on a centennial scale (1900–2010) and identify the potential causes of decadal variations by using an information flow technique. The results indicate that NSWS in the NH experienced a remarkable decadal variation, increasing during 1900–1945 and 1970–1980 and decreasing during 1945–1970 and 1980–2010. Furthermore, regional differences in the distribution features and decadal variations of NSWS were observed. Asia and North America showed the highest data overlap compared to other regions, reaching 59.4%. The longest period of decadal variation in NSWS was found in North America (14 years), followed by Europe (11 years), with Asia showing the smallest period (10 years). When determining the effects of large-scale ocean–atmosphere circulation fields or internal climate models on NSWS changes, prioritising causality between the two variables and the study period is essential, rather than relying solely on simple correlation analysis. According to the information flow technique, the decadal variations in NSWS over North America during 1950–2010 were linked with the Western Hemisphere Warm Pool, whereas the North Atlantic Oscillation influenced those in Europe. The Tropical Northern Atlantic was the driver over Asia. This study offers a scientific foundation for understanding NSWS characteristics on a centennial timescale and the primary causes of decadal variations in NSWS across the NH.